Laboratory Study of Oviposition Preference of Aedes aegypti (Linnaeus, 1762) in Waste Settlement - Hariani, Nova; Syaidah, Eka Rahmawati; Trimurti, Sus (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2019)
This research aims to find out the oviposition ability of Aedes aegypti L. mosquitoes in various settlements wastewater including household waste, industrial laundry, and tofu home industry. The descriptive method was used to count the number of mosquito eggs on each wastewater and to calculate the percentage of survival rate of mosquito from egg to larvae and from larvae to mosquito. Fifty pairs of the Ae. aegypti were applied to modified cageusing three water sources namely household waste, laundry, and tofu industry.In this research, rainwaterwas used as a positive control. The result showed that Ae. aegypti from settlement in Samarinda are able to lay egg in all tested wastes. Laundry wastewater is the most preferred medium based on the number of eggs (6,290 eggs) with percentage of survival rate from egg to larvae is 75.0 % (cage contains one wastewater) and 48.4% (cage contains more than one wastewater) and the percentage of survival rate of larvae become adult mosquitoes phase is 92.8% (cage contains one wastewater) and 90.0% (cage contains more than one wastewater). Keywords: preference, oviposition, Aedes aegypti, wastewater